TRANSFORMASI LAYANAN ADMINISTRASI DIGITAL: SEBUAH KAJIAN INOVASI TEKNOLOGI PENCATATAN SIPIL “KNG” KLAMPID NEW GENERATION DI KOTA SURABAYA - Dalilah, Camilla; Fanida, Eva Hany (Universitas Negeri Surabaya, 2024)
The Surabaya City Department of Population and Civil Registration presents a digital innovation inpopulation and civil registration administration services through an application named